Antiviral Effects of Human Immunodeficiency Virus Type 1-Specific Small Interfering RNAs against Targets Conserved in Select Neurotropic Viral Strains - Dave, Rajnish S. (American Society for Microbiology, 2004)
RNA interference, a natural biological phenomenon mediated by small interfering RNAs (siRNAs), has been demonstrated in recent studies to be an effective strategy against human immunodeficiency virus type 1 (HIV-1). In the present study, we used 21-bp chemically synthesized siRNA duplexes whose sequences were derived from the gp41 gene, nef, tat, and rev regions of viral RNA. These sequences are conserved in select neurotropic strains of HIV-1 (JR-FL, JR-CSF, and YU-2). The designed siRNAs exerted a potent antiviral effect on these HIV-1 strains. The antiviral effect was mediated at the RNA level (as observed by the down-regulation of the HIV-1-specific spliced transcript generating a 1.2-kbp reverse transcription [RT]-PCR product) as well as viral assembly on the cell membrane. Spliced transcripts (apart from the most abundant transcript generating a 1.2-kbp RT-PCR product) arising from an unspliced precursor likely contributed, albeit to a lesser extent, to the antiviral effect. The resultant progeny viruses had infectivities similar to that of input virus. We therefore conclude that these siRNAs interfere with the processing of the unspliced transcripts for the gp41 gene, tat, rev, and nef, eventually affecting viral assembly and leading to the overall inhibition of viral production. Apart from using the gp41 gene as a target, the conservation of each of these targets in the above-mentioned viral strains, as well as several primary isolates, would enable these siRNAs to be used as potent antiviral tools for investigations with cells derived from the central nervous system in order to evaluate their therapeutic potential and assess their utility in inhibiting HIV-1 neuropathogenesis and neuroinvasion.